AUDIT DELAY FACTORS OF INDONESIAN FIRMS: A BINARY LOGIT AND PANEL EGLS ANALYSIS - Ariani, Ade; Sugi, Andi Neneng; Saparudin, Muhammad; Valdiansyah, Riyan Harbi (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This study intends to determine the influence of audit opinion and firm size on audit delays with audit rotation as a mediating variable. We examined 30 firms listed in IDX Circular Letter 2020-2022 using purposive selection and secondary data from financial reports. Despite deadline extensions, these companies consistently needed to submit timely reports. The findings reveal that an unfavorable audit opinion negatively affects the rotation process, whereas a larger firm size has a positive effect. Additionally, audit opinions and rotation negatively affect audit delays, whereas company size has a positive influence. The study also shows that audit rotation partially mediates the association between audit opinion and audit delay and between firm size and audit delay. The research team acknowledges that prevailing economic conditions during data collection may affect the applicability of the results to other periods. This study implies that auditors and accountants identify the primary causes of audit delays, such as inadequate documentation, transaction complexity, and communication issues. Implementing best practices can improve financial reporting quality, reduce errors, and enhance auditor timeliness. Auditors and accountants are advised to adopt these practices to minimize audit delays.